The analytics lifecycle and the age of innovation. Issue 4 (April 2019) - Jewell, Nick
Abstract : A huge number of businesses and organisations of all sizes, from the world's biggest, to small, local companies manage themselves using data to direct their energies. Analytics is at the forefront of modern business management. These are the thoughts that Dave Wells, practice director for data management at Eckerson Group, puts forward in the report 'The New Analytics Lifecycle'. 1 Organisations of all sizes use data to direct their energies. Analytics is at the forefront of modern business management. Yet with the continuing snowballing of data resources, access privileges and the technology stack to support them, security and governance have not been kept top of mind within the analytics lifecycle. An organisation needs to understand from top to bottom the data owners, flows and processes it has and then map onto these new ways of doing business that will keep them compliant and customer-centric, says Nick Jewell of Alteryx.